2018
DOI: 10.5055/jom.2018.0435
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile of intraoperative methadone for analgesia after major spine surgery: An observational study of 1,478 patients

Abstract: Mild-moderate respiratory depression is observed following a one-time dose of intraoperative methadone, and monitoring in an appropriate postoperative setting is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 11 publications
0
21
0
3
Order By: Relevance
“…A retrospective study of 1478 spine surgery patients who received intraoperative methadone demonstrated a relatively high incidence of side effects: 44% of patients presented with nausea/vomiting, 36.8% had respiratory depression, and 80% had hypoxemic events postoperatively. 34 However, the study lacked a comparator group, and methadone dose was not standardized.…”
Section: Conmentioning
confidence: 99%
“…A retrospective study of 1478 spine surgery patients who received intraoperative methadone demonstrated a relatively high incidence of side effects: 44% of patients presented with nausea/vomiting, 36.8% had respiratory depression, and 80% had hypoxemic events postoperatively. 34 However, the study lacked a comparator group, and methadone dose was not standardized.…”
Section: Conmentioning
confidence: 99%
“… 17 Moreover, a single larger dose of intraoperative methadone in adolescents had a high incidence of respiratory depression after PSF. 12 A single dose of intraoperative methadone, as part of a multimodal analgesia regimen, improved pain scores with modest shortening in LOS without significant reduction in opioid consumption on POD 1 and 2. 18 …”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 Some studies suggest postoperative respiratory monitoring is prudent due to high incidence (36.8%) of respiratory depression when used with PCA hydromorphone. 12 However, there is limited evidence for the effectiveness and safety of perioperative methadone in children. Methadone has been effective for postoperative pain in younger children and those undergoing Nuss procedure for surgical correction of pectus excavatum.…”
Section: Introductionmentioning
confidence: 99%
“…Other adverse effects reported as secondary outcomes included hypoxemia (81%), reintubation (2%), naloxone use (2%), hypotension (50%), cardiac arrhythmias (31%), and QTc prolongation (57%) (category B2-E evidence). 113…”
Section: Intraoperative Managementmentioning
confidence: 99%